The management of the British economy, 1945-1960 - Dow, J. C. R. (London Cambridge university press, 1964)
The book is a distinguished contribution to a subject of great practical importance. The book though is about histoty, may appear more an essay in applied economics, with digressions into economic theory.
With a foreword by Sir Robert Hall
aia 25/01/2019
Loans
Keywords: Economic policy; British economy; Great Britain